Effect of Foam Agent & Bioball Addition on Physical and Mechanical Properties of Lightweight Concrete - Tanjaya, Christy Andhika; Supriyadi, Asep; Sutandar, Erwin (Fakultas Teknik Universitas Tanjungpura, 2025)
The growing demand for lightweight building materials that maintain adequate structural integrity has prompted research endeavors into lightweight concrete. This concrete possesses a lower specific gravity compared to conventional concrete, rendering it particularly well-suited for applications in soft soil and peatland environments, such as those prevalent in West Kalimantan. A notable innovation in the development of lightweight concrete involves the incorporation of foam agents and bioballs as supplementary materials, aiming to reduce the overall weight of the mixture without significantly compromising its mechanical properties. This research aims to analyze the effect of the addition of foam agent and bioball on the physical and mechanical properties of lightweight concrete, focusing on volume weight, porosity, compressive strength, split tensile strength, and modulus of elasticity. The research methodology comprised laboratory experiments with variations in the percentage of foam agent and bio ball. Compressive strength, split tensile strength, and modulus of elasticity tests were conducted at 7, 14, and 28 days of concrete age. Additionally, specific gravity and porosity measurements were taken to analyze the impact of additional materials on the physical properties of lightweight concrete. The findings indicated that incorporating foam agent and bioballs in the concrete mixture led to a reduction in the weight content of lightweight concrete to â‰¤ 1850 kg/m ³ and an enhancement in porosity, without substantial compromise to the compressive strength within structural lightweight concrete standards.The optimal amalgamation of foam agent and bioballs yielded lightweight concrete with optimal characteristics in terms of mechanical strength and structural efficiency. Consequently, this renders it a suitable alternative solution for construction applications in areas with low soil bearing capacity, where structural weight reduction is a major factor in design planning.